Modelling household's intentions to adopt hybrid power system in Ghana - Eric Koranteng; Francis Kwesi Bondinuba; Gylbet Camynta-Baezie (Cogent Business & Management, 2024)
The study investigates the factors influencing households' intentions to adopt hybrid power systems in Ghana. Data was collected from 290 households in the Amasaman district using a quantitative survey design. Factors affecting households' intentions included knowledge of the technology, perceived usefulness and benefits, perceived risks and costs, willingness to adopt, age, gender, educational level, religion, household size, type of residence, membership size and energy expenditure. Barriers to adoption included high upfront costs, limited availability of hybrid power systems and inadequate infrastructure. The model predicted that only 44% of households would be willing and intend to use hybrid power systems. The study highlights the role of socioeconomic factors, environmental consciousness and barriers in Ghana's transition to a low-carbon economy. It suggests policymakers and stakeholders should ensure hybrid power systems' financial and social acceptability. Limitations include focusing on intentions rather than adoption rates, potential response bias and measurement error. Recommendations include targeted policies, financial incentives, infrastructure development and awareness campaigns. The study contributes to Ghana's sustainable development goals by promoting reliable, clean electricity, particularly in rural areas with limited grid connectivity, aligning with the United Nations Sustainable Development Goals.
Keywords: 650; Ghana; households; hybrid power; intention; modelling